The Influence of Market Orientation and Entrepreneurship Orientation on Marketing Performance of Culinary SME`s in Semarang City - Misbakhul Arrezqi; Bagus Yunianto Wibowo (IAIN Palopo, 2021)
This study analyzes the effect of market orientation and entrepreneurial orientation on the marketing of culinary micro, small and medium enterprises (SME`s) in Semarang City. The aim of this research is: (1) Determine the effect of market orientation on market efficiency (2) Determine the effect of business orientation on market efficiency. By using quantitative descriptive research, the sampling technique used in this research is saturated sampling method. The data obtained in this study were obtained by distributing questionnaires to 100 culinary MSME respondents registered in the city of Semarang. SEM Paket Amos 24.0 is used as an analytical tool. The results of the research obtained are (1) Marketing orientation has a positive and significant effect on the performance of MSME culinary marketing (2) Entrepreneurial orientation has a positive and significant effect on the performance of MSME culinary marketing.